2018
DOI: 10.1007/s00128-018-2392-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Temperature-Dependent Changes in the Characteristics of Biochar-Borne Dissolved Organic Matter and Its Copper Binding Properties

Abstract: The dissolved organic matter (DOM) samples from biochars produced from Jerusalem artichoke stalks by pyrolysis at 300, 500, and 700 °C were characterized using a combination of spectroscopic techniques. Additionally, the binding affinities (long K) and the complexation capacities (C) of the DOM samples with Cu(II) were calculated to assess their Cu binding properties. The biochar-borne DOM contained mainly humic-like components (C1-C3) with a small amount of a protein-like component (C4). As the charring tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…With a rise in pyrolysis temperature, DOM released from RSC biochars quickly decreased from 2.73 ± 0.19 g C/kg in RSC300 to 0.19 ± 0.001 in RSC500 and 0.13 ± 0.02 g C/kg in RSC700 (Table 1). This trend was also observed for biochars produced from other lignocellulose-rich feedstocks, such as Jerusalem artichoke stalks (Wei et al, 2019a), rice straws (Xiao et al, 2014), and wetland plant litters (Wu et al, 2019). DOM content in biochar was primarily affected by pyrolysis temperature and feedstock.…”
Section: Dom Content In Biochars As Affected By Pyrolysis Temperaturementioning
confidence: 69%
See 3 more Smart Citations
“…With a rise in pyrolysis temperature, DOM released from RSC biochars quickly decreased from 2.73 ± 0.19 g C/kg in RSC300 to 0.19 ± 0.001 in RSC500 and 0.13 ± 0.02 g C/kg in RSC700 (Table 1). This trend was also observed for biochars produced from other lignocellulose-rich feedstocks, such as Jerusalem artichoke stalks (Wei et al, 2019a), rice straws (Xiao et al, 2014), and wetland plant litters (Wu et al, 2019). DOM content in biochar was primarily affected by pyrolysis temperature and feedstock.…”
Section: Dom Content In Biochars As Affected By Pyrolysis Temperaturementioning
confidence: 69%
“…DOM in the biochar actually was consisted of both original components in the feedstock and pyrolysis products, such as humicand protein-like substances, which have been identified by a variety of spectroscopic and mass spectrometric techniques (Li et al, 2017;Qu et al, 2016;Smith et al, 2016;Uchimiya et al, 2013). Numerous studies have indicated that the chemical compositions of DOM varied greatly from the feedstocks and pyrolysis temperatures of biochar, as well as the extraction protocols (Lee et al, 2018;Wei et al, 2019a;Wu et al, 2018). Among these parameters, pyrolysis temperature was usually a vital determinant of the DOM characteristics (Liu et al, 2019;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second factor, which strongly affects both the qualitative and quantitative composition of PAHs, and the lipid component of product, is the pyrolysis process [8]. The main danger to humans is the carcinogenic, immunotoxic, teratogenic properties of PAHs.…”
Section: Introductionmentioning
confidence: 99%